Grunderwerbsteuer: Finanzministerium plant Möglichkeit zur Abschaffung - Christian Rasquin (Wirtschaftsdienst, 2023)
– The Federal Ministry of Finance wants to allow German Federal States to lower the property transfer tax rates for owner-occupied housing. There is evidence that such tax heavily distorts the housing market. However, since the tax is an important source ofrevenue for the Federal States, it remains to be seen whether these will cut tax rates.
Keywords: H21; H77; R31; 330; Grunderwerbsteuer; Deutschland; Grunderwerbsteuer; Deutschland